2013
DOI: 10.1155/2013/909302
|View full text |Cite
|
Sign up to set email alerts
|

A Rare Cause of Dyspnea: Sudden Rupture of Aortic Valsalva Sinus Aneurysm

Abstract: Aneurysm of the sinus of Valsalva is an uncommon cardiac abnormality; however, the most common complication is rupture into the right heart chambers or rarely towards the left chambers. A ruptured aneurysm typically leads to an aortocardiac shunt and progressively worsening heart failure. We report a case of a 21-year-old male who suffered an aneurysm of the sinus of Valsalva rupture into the right atrium who underwent successful surgical repair.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
13
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(13 citation statements)
references
References 9 publications
0
13
0
Order By: Relevance
“…However, the challenge is to establish an early and accurate diagnosis; these aneurysms are typically clinically silent until they rupture. 3 Rarely, SVAs can lead to myocardial ischemia, either by directly compressing a coronary artery or by thrombotic embolization. 1,2,8,9 Ruptured SVAs typically present in the 3rd or 4th decade of life with nonspecific symptoms, including chest pain, dyspnea, and fatigue.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, the challenge is to establish an early and accurate diagnosis; these aneurysms are typically clinically silent until they rupture. 3 Rarely, SVAs can lead to myocardial ischemia, either by directly compressing a coronary artery or by thrombotic embolization. 1,2,8,9 Ruptured SVAs typically present in the 3rd or 4th decade of life with nonspecific symptoms, including chest pain, dyspnea, and fatigue.…”
Section: Discussionmentioning
confidence: 99%
“…8 However, presentation and hemodynamic stability depend on the involved sinus and the vector of the consequent shunt within the associated cardiac chamber. 3,4 Regardless, heart failure will occur within hours or weeks. 2,9 Many authors have reported single sinus aneurysms.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…6 These aneurysms are typically congenital and are associated with ventricular septal defects (40% of patients) and aortic regurgitation (30% of patients). [6][7][8] Acquired SVAs are also associated with bacterial endocarditis and syphilis. 5 The major complication of a SVA is rupture into the right heart chambers, or rarely into the left chambers.…”
Section: Discussionmentioning
confidence: 99%